Proposed new interior design scheme of Spa Origins Esthetics International Group Berhad (EIG) Lot 175, Jalan Maarof, Bangsar, 59000 Kuala Lumpur / Noralina Adnan - Adnan, Noralina (Faculty of Architecture, Planning and Surveying, 2011)
This final project for students of Diploma in Interior Design is a manifestation of the student’s knowledges and understandings about all of the interior design aspects that they had learned for three years, from the early stages to the final design presentation process. My final project entitled ‘Proposed New Interior Design of Origins’ Spa for Esthetics International Group Berhad [EIG] at Lot 175, Jalan Maarof, Bangsar, 59000 Kuala Lumpur. The proposed spa is a beauty and health care center which provides a variety of treatments and services for their customers. As the target market is mainly men and women between average to elite level, the design should not only be fine-looking, but also suits their needs and desires. The selected concept and image should reflects Origins’ corporate identity, and at the same time gives a positive impact and effect to the customers. Therefore, the chosen design style for Origins’ Spa is ‘modern tropical’, which basically means a modern design with a touch of nature and tropical elements. However, before selecting the design style for Origins’ Spa that best reflects the client’s corporate identity, some researches has been done in order to identify the target market of Origins’ Spa. Among the research concludes treatment packages offered, basic space requirements of a spa, types of services offered, business hours, and other useful information about spa. In order to complete this thesis report, some researches have also been done through interviews, information gained from mass media, the internet, the official website of Origins, the fan page of Origins in Facebook, survey forms, case study of local and international spa design, operational and administational system and several other methods. This researches help gives me useful, new information on spa as well as will eventually helps me in design process.